Problems of economic security management of the enterprises of the aviation industry - I. I. Zvyagintseva; T. I. Zueva (Управление)
The modern conditions caused by an unstable geopolitical and economic situation in the country and the world stimulate carrying out researches in the field of ensuring economic security of the enterprises of high-tech industries, such as aviation, defensive industry, space branch. Studying of the matter will allow developing the effective mechanism of ensuring economic security of the enterprise taking into account specifics of activity of the enterprises of high-tech industries, in the conditions of uncertainty. In the article the problems of current state of economic security at the enterprises of aviation industry have considered. The relevance of this research is confirmed by the fact, that in the conditions of active integration between the enterprises within the country and also within interstate cooperation on a number of aviation projects, development of communications between the enterprises bears in itself the certain risks having significant effect on a condition of economic security of the enterprises in general and implementation of aviation projects in particular. In such conditions the enterprises need to manage economic security. In this research the problem of management of safety has offered to be solved in a uniform risk management system of the enterprises of aviation industry. The article substantiates the role and place of risk management in the procedure of ensuring economic security and stable sustainable development of the enterprise, taking into account the specifics of risk management of aviation enterprises. Solving the problem of economic security at the enterprise level is a priority, especially when you consider that this level of security is currently the least studied methodologically. Risk management is an integral part of ensuring the safety of the enterprise, the main task of which is to ensure the predictability of the predicted results.